2024
DOI: 10.3390/s24020508
|View full text |Cite
|
Sign up to set email alerts
|

GNSS Radio Frequency Interference Monitoring from LEO Satellites: An In-Laboratory Prototype

Micaela Troglia Gamba,
Brendan David Polidori,
Alex Minetto
et al.

Abstract: The disruptive effect of radio frequency interference (RFI) on global navigation satellite system (GNSS) signals is well known, and in the last four decades, many have been investigated as countermeasures. Recently, low-Earth orbit (LEO) satellites have been looked at as a good opportunity for GNSS RFI monitoring, and the last five years have seen the proliferation of many commercial and academic initiatives. In this context, this paper proposes a new spaceborne system to detect, classify, and localize terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that RSs are still by far the most effective tools for in situ atmospheric temperature observations, but operational meteorological satellites are gradually closing the gap despite their reliance on in situ data for their calibration and validation [77,146,151]. For instance, there have been great advances in RS [141,173] and satellite technology [174]. Manufacturers have been at the forefront of these developments, and they incorporate new models into the market as soon as they become available.…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%
“…Studies have demonstrated that RSs are still by far the most effective tools for in situ atmospheric temperature observations, but operational meteorological satellites are gradually closing the gap despite their reliance on in situ data for their calibration and validation [77,146,151]. For instance, there have been great advances in RS [141,173] and satellite technology [174]. Manufacturers have been at the forefront of these developments, and they incorporate new models into the market as soon as they become available.…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%